2021
DOI: 10.1016/j.earscirev.2021.103617
|View full text |Cite
|
Sign up to set email alerts
|

Lost islands in the northern Lesser Antilles: possible milestones in the Cenozoic dispersal of terrestrial organisms between South-America and the Greater Antilles

Abstract: Our study aims to reconstruct the palaeogeography of the northern part of the Lesser Antilles in order to analyse whether emerged areas might have existed during the Cenozoic, favouring terrestrial faunal dispersals between South America and the Greater Antilles along the present-day Lesser Antilles arc. The stratigraphy and depositional environments of the islands of Anguilla, St Martin, Tintamarre, St Barthélemy, Barbuda and Antigua are reviewed in association with multichannel reflection seismic data acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 85 publications
(85 reference statements)
5
70
0
Order By: Relevance
“…Such behaviour is often observed with some biotic components on remote islands/island groups that have never been connected to the mainland (e.g. Galápagos, Hawaii), or that were in the past were largely/wholly F I G U R E 1 Map of the Caribbean showing the physiographical features mentioned in the text plus the study areas of Garrocq et al, (2021), Cornée et al, (2020Cornée et al, ( , 2021 and Philippon et al, (2020). The base image was generated using GeoMapApp (Ryan et al, 2009).…”
Section: Te S Ting G a Arl Andiamentioning
confidence: 99%
“…Such behaviour is often observed with some biotic components on remote islands/island groups that have never been connected to the mainland (e.g. Galápagos, Hawaii), or that were in the past were largely/wholly F I G U R E 1 Map of the Caribbean showing the physiographical features mentioned in the text plus the study areas of Garrocq et al, (2021), Cornée et al, (2020Cornée et al, ( , 2021 and Philippon et al, (2020). The base image was generated using GeoMapApp (Ryan et al, 2009).…”
Section: Te S Ting G a Arl Andiamentioning
confidence: 99%
“…In sedimentary basins, σ1 is generally vertical and corresponds to the lithostatic vertical stress (σv) and we assume here that σ2 and σ3 are respectively perpendicular and parallel to the short axis of best fit ellipses obtained from the center-to-center method. In the north, the PFS abruptly ends at the toe of Saba Bank, a lithified reefal and red algal platform (Cornée et al, 2021) >The basement remains high in the NGB, reaching a maximum of about 4 s TWT in depth, although it is strongly deepening in the SGB, reaching a maximum of 10 s TWT (Figures 11a). The different subsidence histories have strongly influenced the architecture of both basins with the SGB deepening toward a curved depocenter more or less parallel to the volcanic arc whereas the NGB remains relatively flat and high (Figures 11b).…”
Section: Evolutionary Model Of Polygonal Faults In the Grenada Basinmentioning
confidence: 99%
“…Ar ages Nagle et al, 1976Briden et al, 1979Davidson et al, 1993Cornée et al, 2021 This study structural measure observed fault well normal fault…”
Section: Terres-basses Peninsula Sm4mentioning
confidence: 88%